Sistema de Realidad Virtual Para Entrenamiento y Análisis Biomecánico de Pacientes Con Amputación Transhumeral - Rodal Martinez, Francisco Javier; Quiñones Urióstegui, Ivett; Galván Dúque Gastélum, Carlos; Vilchis Zapata, Carlos Leonel (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Virtual Reality is defined as an interactive and multisensory computer system in which an environment is simulated in real time, and there can be two categories: Immersive Virtual Reality and Non-Immersive Virtual Reality. To date, Virtual Reality has been used in different areas such as education, entertainment and rehabilitation. The WHO estimates that around 15% of the world’s population suffers from a disabling condition. This organization in conjunction with the ISPO determined that about 0.5% of the world’s population requires an orthotic or prosthetic system. In Mexico, in the National Survey of Demographic Dynamics it is estimated that 10.9% of the population has difficulty walking or moving. The objective of this project is to design a Virtual Reality system that allows training transhumeral amputees in the use of the prosthesis. 2 virtual environments and 8 3D-characters were created so that the subjects to be trained can select between these possibilities to carry out the training sessions. The subjects control these 3D-characters in real time through a motion capture system, which also generates a biomechanical analysis of the movement of the shoulder during the execution of the movements.